HUBUNGAN STATUS GIZI DENGAN TINGKAT KESEGARAN JASMANI SISWA DI SD NEGERI 2 LUBUK MUDA - Zubaidah, Zubaidah; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation or observation by the author in the field, that the level of physical fitness of students at SDN 2 Lubuk Muda still low. Many factors lead to low levels of physical fitness that include nutritional status. So the purpose of this study was to determine the relationship of nutritional status and physical fitness level of students at SDN 2 Lubuk Muda. This type of research is correlational. The population in this study all students at SDN 2 Lubuk Muda, amounting to as many as 119 people. The sampling technique used purposive sampling. Thus the sample in this study amounted to as many as 46 people, with details of 26 male students and 20 female students. The data collected by measuring the two variables. for nutritional status by testing antrophometri. Meanwhile, to obtain data on physical fitness physical fitness tests Indonesia. Data were analyzed using product moment correlation. Based on the analysis of data obtained relationship with the nutritional status of students' physical fitness level 2 Lubuk Muda Elementary School, for the son obtained rhitung 0.436> 0.388 rtabel, female students obtained rhitung 0.477> 0.444 rtabel, and accepted as true empirically. This means that there is a significant relationship (significant) between nutritional status and physical fitness accepted as true by the real (empirical).Keywords : nutritional status, physical fitness